Black lies, red blood - Eriksson, Kjell, 1953- (Eriksson, Kjell, 1953- Ann Lindell, 2014)
Uppsala, Sweden. Inspector Ann Lindell has little time to enjoy her new relationship with journalist Anders Brant before he leaves on an assignment, and she is called upon to investigate the disappearance of a young woman, Klara Lovisa Bolinder. When Lindell's colleagues discover the body of a murdered homeless man, the evidence suggests that Brant could be involved. Lindell is forced to battle her fears about her relationship if she is to discover what happened to Klara, and as the Uppsala Police Department unearth more information about the homeless man, they fear they may be looking for a serial killer.